Defect recognition in crystalline silicon solar cells by X-ray tomosynthesis with layer resolution - Voland, Virginia; Hoyer, Ulrich; Auer, Richard; Salamon, Michael; Uhlmann, Norman; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2015)
The increasing demand for higher quality in solar cell production led to the development of several inline control methods. Beneath the image-guided methods, X-ray is not yet very well investigated for the application in photovoltaic research but shows high potential. In contrast to the ordinary X-ray radioscopic method, the tomosynthesis technique exhibits additional depth information of the solar cells and modules. In this article, several applications of tomosynthesis for the investigation of solar cells and modules are studied. It will be shown what potential the application of X-ray and especially tomosynthesis has as quality control tool for photovoltaics.
Keywords: Defect recognition; Metrology; Tomosynthesis; X-ray